1976
DOI: 10.1021/bi00650a013
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thyroid hormones on the level of the hepatic mRNA for α2u globulin

Abstract: A procedure is presented for the purification of alpha2u globulin, a protein synthesized in the liver, secreted into the serum, and excreted in the urine of male rats. The steady-state levels of alpha2u globulin in the serum and liver cytosol fraction of adult male rats have been determined using a radial immunodiffusion assay. A cell-free protein synthesizing system, easily prepared from commercial wheat germ, has been used to identify and quantitate the mRNA coding for alpha2u globulin. Poly(A)-containing RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
58
0

Year Published

1977
1977
2000
2000

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 202 publications
(60 citation statements)
references
References 26 publications
2
58
0
Order By: Relevance
“…Linearity with respect to the amount of cell-free products synthesized in response to GC cell RNA was also obtained when these products were mixed in different (2) precipitate with antiserum to prolactin; (3) no treatment; (4) precipitate with antisera to prolactin and growth hormone; (5) supernatant medium after precipitation with antiserum to growth hormone; and (6) precipitate with antiserum to growth hormone. (7)(8)(9) The released chains obtained after translation of RNA from GC cells: (7) precipitate with antiserum to bovine serum; (8) no treatment; or (9) precipitate with antiserum to growth hormone. GH, growth hormone; pGH, pregrowth hormone; PL, prolactin.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Linearity with respect to the amount of cell-free products synthesized in response to GC cell RNA was also obtained when these products were mixed in different (2) precipitate with antiserum to prolactin; (3) no treatment; (4) precipitate with antisera to prolactin and growth hormone; (5) supernatant medium after precipitation with antiserum to growth hormone; and (6) precipitate with antiserum to growth hormone. (7)(8)(9) The released chains obtained after translation of RNA from GC cells: (7) precipitate with antiserum to bovine serum; (8) no treatment; or (9) precipitate with antiserum to growth hormone. GH, growth hormone; pGH, pregrowth hormone; PL, prolactin.…”
Section: Resultsmentioning
confidence: 99%
“…Although little is known about the mechanism of thyroid hormone action, the discovery of nuclear receptors (4, 5) that are DNA-binding proteins (6) and Tata's report (7) of changes in total RNA synthesis in response to thyroid hormone have directed attention to chromatin as one possible site of hormonal control. Further, recent cell-free translational data have shown that hepatic a2u globulin mRNA is increased in thyroid hormone-treated animals (8,9). This system is somewhat complicated because at least four hormones are required, the kinetics are slow, and the stimulations have been performed in animals in which primary hormone influences have not been differentiated from secondary influences.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Thyroid hormone and androgenic steroids appear to act in a concerted fashion to influence the in vivo synthesis of rat liver a2u-globulin. The induction of a2u-globulin by thyroid hormone and androgenic steroids parallels the change in the hepatic levels of a2u globulin mRNA (25). Whether the multihormonal regulation of specific mRNA levels by thyroid and steroid hormones reflects a common control mechanism that applies to other thyroid and steroid hormone responsive systems will require further study.…”
Section: Discussionmentioning
confidence: 97%
“…Later, DeGroot et al and Dilman et al showed increase in the poly(A)-rich fraction of RNA (2,3). Demonstrations of stimulation of a specific mRNA by thyroid hormones were recently provided by Kurtz et al (4) and by Roy et al (5) for a2u-globulin in the rat. However, because a number of hormones are known to stimulate the synthesis of this protein (6) and because thyroid hormone profoundly alters the level of such hormones (7), experiments done in the whole animal do not provide sufficient evidence for the direct induction of -d2u-globulin mRNA by thyroid hormone.…”
mentioning
confidence: 91%